2017
DOI: 10.1055/s-0037-1604114
|View full text |Cite
|
Sign up to set email alerts
|

Management of Polypoid Gallbladder Lesions in Children: A Multicenter Study

Abstract: This report confirms appropriate use of a conservative approach with annual clinical and ultrasound follow-up for small-sized and isolated PLG in children given the absence of malignancy and potential vanishing entities. Surgical treatment should be considered in case of lesions larger than 10 mm in size or when they are associated with symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…In the current study, 80% of the patients were girls. In a report of 18 child GP patients by Ballouhey et al (12), 13 (72.2%) were girls at similar rates to those of the current study. In addition, female frequency of adult patients with GP in studies by Terziog ˘lu et al (18) and Guo et al (29) have been reported as 67.3% and 56.3%, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the current study, 80% of the patients were girls. In a report of 18 child GP patients by Ballouhey et al (12), 13 (72.2%) were girls at similar rates to those of the current study. In addition, female frequency of adult patients with GP in studies by Terziog ˘lu et al (18) and Guo et al (29) have been reported as 67.3% and 56.3%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, there was no case of cholelithiasis and any associated cholecystitis. Ballouhey et al (12) found 2 (11%) patients with pseudopolyp and the lesions regressed in follow‐ups. In our study, no pseudopolyp was detected in any patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations